Gatekeeper Training for Suicide Prevention A Theoretical Model and Review of the Empirical Literature - Burnette, Crystal (RAND Corporation, 2015)
In recent years, the rising rate of suicides by military personnel has generated concern among policymakers, military leaders, and the public at large. Based on a recommendation from an earlier RAND report on preventing suicide among military personnel, this report reviews the literature on gatekeeper models of suicide prevention to better understand what is known about the effectiveness of gatekeepers and gatekeeper training.